Global Variability in Administrative Approval Prescription Criteria for Biologic Therapy in Severe Asthma - Porsbjerg, Celeste M; Menzies-Gow, Andrew N; Tran, Trung N; Murray, Ruth B; Unni, Bindhu; Audrey Ang, Shi Ling; Alacqua, Marianna; Al-Ahmad, Mona; Al-Lehebi, Riyad; Altraja, Alan; Belevskiy, Andrey S; Björnsdóttir, Unnur S; et al. (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2022)
Regulatory bodies have approved five biologics for severe asthma. However, regional differences in accessibility may limit the global potential for personalized medicine. To compare global differences in ease of access to biologics. In April 2021, national prescription criteria for omalizumab, mepolizumab, reslizumab, benralizumab, and dupilumab were reviewed by severe asthma experts collaborating in the International Severe Asthma Registry. Outcomes (per country, per biologic) were (1) country-specific prescription criteria and (2) development of the Biologic Accessibility Score (BACS). The BACS composite score incorporates 10 prescription criteria, each with a maximum score of 10 points. Referenced to European Medicines Agency marketing authorization specifications, a higher score reflects easier access. Biologic prescription criteria differed substantially across 28 countries from five continents. Blood eosinophil count thresholds (usually ≥300 cells/μL) and exacerbations were key requirements for anti-IgE/anti-IL-5/5R prescriptions in around 80% of licensed countries. Most countries (40% for dupilumab to 54% for mepolizumab) require two or more moderate or severe exacerbations, whereas numbers ranged from none to four. Moreover, 0% (for reslizumab) to 21% (for omalizumab) of countries required long-term oral corticosteroid use. The BACS highlighted marked between-country differences in ease of access. For omalizumab, mepolizumab, benralizumab, and dupilumab, only two, one, four, and seven countries, respectively, scored equal or higher than the European Medicines Agency reference BACS. For reslizumab, all countries scored lower. Although some differences were expected in country-specific biologic prescription criteria and ease of access, the substantial differences found in the current study present a challenge to implementing precision medicine across the world.